Primerjava in razvoj naprav za oblaganje delcev - Luštrik, Matevž (Farmacevtski vestnik, 2010)
Particle coating technology is a process that is being used in pharmaceutical industry for many decades. Particles are coated with the purpose of taste masking of unpalatable substances, protection from light, moisture and oxygen from the atmosphere surrounding the particles, aesthetic reasons, better acceptance by users and modified release. In this article the coating process is presented in term of process equipment. Various process equipment can be used for particle coating, which is in general divided to coating drums and fluid bed devices. The first part comprehends some of the most important improvements in drum coating technology. Additionaly the fluid bed technology is described together with certain device subtypes that have enabled more efficient coating deposition and production of high quality and uniformly coated particles.
Keywords: bobni za oblaganje; granuliranje; oblaganje majhnih delcev; razprševanje